Testing of January Effect, the Day of the Week Effect, and Size Effect: a Study of LQ45 Stocks in Indonesia Stock Exchange - Hendrawaty, Ernie; Huzaimah, Raden Ayu Fiska (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
The purpose of this study is to examined the anomalies on the efficient capital market. However, research that combines January Effect, the day of the week Effect, and size Effect of getting a complete and clear picture of the phenomenon on the market is still limited. The variables used are stock returns, trading days, company size. This study uses linear panel regression. The January Effect hypothesis in The Indonesian Capital Market does not support, whereas the combined test conducted to differentiate the behavioral pattern of the days of the week Effect and the size Effect in January and Non-January months.Ã‚Â The study proved the hypothesis which states that seasonal pattern dominated occurs in January trading months, while the size pattern occurs in Non-January trading months. In the future, the arguments about the emergence of the day of the week Effect phenomenon in the Indonesian capital market by revealing the role of investors and essential information as factors that cause the phenomenon to arise. Further studies should continue to use all listed stocks but use a more extended period.